Architectural environment of the North: Problems and prospects - Максим Винницкий; Алексей Меренков (Проект Байкал)
The article presents an overview of some modern problems that people face in the northern regions. The emphasis is on problems in the solution of which a significant role should be given to architecture and urban planning. The principles of forming the architectural environment of northern settlements are developed by the authors, interpreted for the specific natural and climatic conditions of the northern regions and proposed as tools for solving the identified problems. The possible positive effect of applying these principles is revealed, primarily in the aspect of creating a comfortable environment for northern cities that supports the physical and psychological health of people in the North. The authors give examples of experimental projects of USUAА students for harsh conditions of northern settlements.